Analysis of Heavy Metal Content of Copper (Cu) in Milkfish (Chanos chanos Forsk) from Milkfish Farms in Bima Bay 2020 - Muhamad Alfian Yunanmalifah; khairuddin khairuddin; M. Yamin (Jurnal Biologi Tropis, 2021)
Fish are aquatic organisms and are often used as biological indicators of heavy metals in waters, because fish belong to the highest trophic level and their nature is to settle in certain habitats. This research aims to explore the Cu content in milkfish from the Bima Bay milkfish aquaculture to determine the copper content in milkfish from the Bima Bay milkfish aquaculture. The usefulness of this research is to provide information on the Cu content of milkfish aquaculture in Bima Bay. This research was conducted for four months, starting from February - June 2021. Sampling was carried out by purposive sampling at 2 location points with three repetitions. Samples were analyzed at BLKPK NTB Province using the Atomic Absorption Spectrophotometry tool. The results showed that the Cu Content in Palibelo ranged from 0.814 mg/kg (ppm) to 0.915 mg/kg (ppm), so that an average of 0.856 mg/kg (ppm) was obtained. Meanwhile, the Cu Content in Melayu ranged from 0.351 mg/kg (ppm) to 0.441 mg/kg (ppm), so that an average of 0.387 mg/kg (ppm) was obtained. The average total Cu content in milkfish in the Bima Bay area is 0.621 mg/kg (ppm). Based on these results, it can be concluded that the Cu content in milkfish meat from milkfish aquaculture in Bima Bay is 0.621 mg/kg (ppm). The content is very far below the threshold according to the Regulation of the Dirjen POM No.03725/B/SK/VII/89 which is 20 mg/kg so that it is safe for consumption by the public.